Combining the previous measure of evidence to educational entrance examination - Maseleno A.; Huda M.; Siregar M.; Ahmad R.; Hehsan A.; Haron Z.; Ripin M.N.; Ihwani S.S.; Jasmi K.A. (Asian Network for Scientific Information, 2024)
Indexed by SCOPUS